2013
DOI: 10.1016/j.vaccine.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Basophils help establish protective immunity induced by irradiated larval vaccination for filariasis

Abstract: Basophils are increasingly recognized as playing important roles in the immune response towards helminths. In this study, we evaluated the role of basophils in vaccine-mediated protection against filariae, tissue-invasive parasitic nematodes responsible for diseases such as elephantiasis and river blindness. Protective immunity and immunological responses were assessed in BALB/c mice vaccinated with irradiated L3 stage larvae and depleted of basophils with weekly injections of anti-CD200R3 antibody. Depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…80 Basophils also contribute to protection against the filarial nematode Litomosoides sigmodontis when mice were immunized with irradiated larvae. 81 Thus basophils play a critical role in acquired immunity against helminth infections. Basophils also show some contribution in mice to the protective immunity in primary infection with Strongyloides ratti or Strongyloides venezuelensis.…”
Section: The Beneficial Role Of Basophils In Protective Immunity Agaimentioning
confidence: 99%
“…80 Basophils also contribute to protection against the filarial nematode Litomosoides sigmodontis when mice were immunized with irradiated larvae. 81 Thus basophils play a critical role in acquired immunity against helminth infections. Basophils also show some contribution in mice to the protective immunity in primary infection with Strongyloides ratti or Strongyloides venezuelensis.…”
Section: The Beneficial Role Of Basophils In Protective Immunity Agaimentioning
confidence: 99%
“…Basophils are an important component of the immune response to helminth infections . Basophils gained prominence because of their potential role in Th2 cell differentiation as the initial source of ‘innate’ IL‐4 that was capable of driving a Th2 response in murine models of helminth infection but also of inducing AAMs.…”
Section: Host‐related Factors In Immune‐mediated Modulationmentioning
confidence: 99%
“…Despite previous studies using depleting Abs that suggested a role of basophils during Th2 T cell priming, Th2 T cell expansion was not affected in (22). During infection with L. sigmodontis, basophils were reported to participate in the protective immunity induced by vaccination with irradiated larvae, which results in a 70% reduction of the worm burden (12). We evaluated the establishment of immunity induced by vectortransmitted L3 to mimic the natural situation.…”
Section: Discussionmentioning
confidence: 98%
“…During infection with the tissue-dwelling L. sigmodontis, basophils were proposed to amplify the type 2 immune response without having an impact on the course of primary infection (11). However, depletion of basophils prior to vaccination with irradiated larvae altered the worm burden in a challenge infection (12), suggesting a central role for basophils in immune memory formation to tissue dwelling helminths.…”
Section: Introductionmentioning
confidence: 99%